Resistance training for adolescents - Miller, M. G.; Cheatham, C. C.; Patel, N. D. (Pediatric Clinics of North America, 2010)
The benefits and possible detriments of resistance training have been noted extensively in the literature. Although the benefits of resistance training are well known, many professionals fail to heed scientific advice or follow appropriate recommendations for resistance training in adolescents. When developing a resistance training program for adolescents, be cognizant of any pre-existing health conditions and experience level of the adolescent. For strength training, the adolescent should begin with exercises that involve all major muscle groups with relatively light weight, one to three sets of 6 to 15 repetitions, 2 to 3 non-consecutive days per week. As the adolescent becomes more experienced, gradually increase loads and add multijoint exercises. Each exercise session should be properly supervised for safety, and to provide feedback on technique and form, regardless of the resistance training experience of the adolescent. This article reviews the guidelines for resistance training for health-related fitness for adolescents.